Factors affecting Umbilical Cord Vitamin D Concentration and Its Association with Maternal Vitamin D Level - Aggarwal, Aditya; Modi, Amit Kumar; Singh, K. Rimi; Jha, Avinash Kumar (International Journal of Integrated Health Sciences, 2024)
Objective: To analyze factors affecting maternal and umbilical cord levels of vitamin D and to understand the correlation between maternal and umbilical cord vitamin D levels.Methods: This was a cross-sectional study conducted at the department of pediatrics of Dr. D. Y. Patil Medical College and Research Centre, Pune, India. Maternal and umbilical cord vitamin D levels were examined in 300 pairs of mother and child over a period of two years. Informed consent was obtained from all participants. The vitamin D level was measured using chemiluminescent immunoassay and classified as either deficient, insufficient or adequate depending on specific cut-offs. Correlations between maternal and neonatal vitamin D levels and demographic factors like religion, socioeconomic status, and sun exposure were also exlored. Statistical tests were performed using the SPSS 21.0 software, with p<0.05 deemed P-valueas significant.Results: There was significantly high prevalence of vitamin D deficiency in neonates, (78.67%). Key factors influencing maternal vitamin D levels were religion (p=0.027), maternal education (p=0.003), gravida status (p=0.035), and sunlight exposure, with sunlight exposure showing a very strong correlation to the deficiency (p<0.001). Moreover, maternal serum calcium levels significantly affected vitamin D status (p<0.001). A significant association was observed between maternal and cord blood vitamin D levels, with the maternal vitamin D level strongly predicted vitamin D status in neonates (p<0.001).Conclusion: The umbilical cord vitamin D level strongly correlates with the maternal vitamin D level, which is  significantly affected by maternal education, residence, pregnancy status, gestational age, and sun exposure.